2019
DOI: 10.24221/jeap.4.4.2019.2633.297-303
|View full text |Cite
|
Sign up to set email alerts
|

Effect of indolebutyric acid on rooting and budding of cuttings of Glyicidium sepium

Abstract: Studies carried out with the use of gliricidia biomass found that green manure contributes to increasing the productivity of forest crops when compared to the incorporation of other legumes. This study aimed to evaluate the viability of vegetative propagation by cuttings in the development of rooting and budding of Glyicidium sepium in different concentrations of indolebutyric acid (IBA). The experiment was carried out in a greenhouse with an entirely randomized block design and increasing concentrations of IB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Although several authors in studies with IBA use in plants of the family Melastomataceae, observed increase in the rooting percentage of many species (Engel et al, 2017;Penso et al, 2016;Pizzatto et al, 2011, Suzuki et al, 2015, each species has specific peculiarities about rooting and propagation of cuttings, such as genetic factors and quantity of endogenous auxins. The authors Latoh et al (2018) tested exogenous auxins in several species of Tibouchina and concluded that T. affinis, T. heteromalla and T. moricandiana do not need exogenous auxins to induce rooting, T. granulosa can root when treated with IBA, however, T. sellowiana is a hard to root species, and even when treated with IBA, do not develop adequate roots.…”
Section: Tibouchina Dubia Cognmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several authors in studies with IBA use in plants of the family Melastomataceae, observed increase in the rooting percentage of many species (Engel et al, 2017;Penso et al, 2016;Pizzatto et al, 2011, Suzuki et al, 2015, each species has specific peculiarities about rooting and propagation of cuttings, such as genetic factors and quantity of endogenous auxins. The authors Latoh et al (2018) tested exogenous auxins in several species of Tibouchina and concluded that T. affinis, T. heteromalla and T. moricandiana do not need exogenous auxins to induce rooting, T. granulosa can root when treated with IBA, however, T. sellowiana is a hard to root species, and even when treated with IBA, do not develop adequate roots.…”
Section: Tibouchina Dubia Cognmentioning
confidence: 99%
“…In Brazil are found 23 species, most of them inhabiting the Southern States. The species richness is found on South Brazilian Plateau, at altitudes ranging above 900m (Stehmann, 2019). Calibrachoa sellowiana has infundibuliform corola, externally hairy, internally papillae near anthers, tube with 9-15(20) mm of length, yellow with purple striatedreticulated venation, yellow fauce, blade with 15-30 mm of diameter, magenta or purple color (Stehmann, 2019).…”
Section: Introductionmentioning
confidence: 99%